2019
DOI: 10.1186/s13046-019-1112-4
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor-α-miR-1271-SNAI2 feedback loop regulates transforming growth factor-β-induced breast cancer progression

Abstract: Background Breast cancer is the most common cancer among women worldwide, and approximately 70% of breast cancers are hormone receptor-positive and express estrogen receptor-α (ERα) or/and progesterone receptor. ERα has been identified to promote the growth of primary breast cancer, however, it can also antagonize signaling pathways that lead to epithelial-mesenchymal transition (EMT), including transforming growth factor-β (TGF-β) signaling. miRNA alteration or dysfunction is involved in cancer d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
(45 reference statements)
0
18
0
Order By: Relevance
“…SNAI2 (also known as Slug), a member of Snail superfamily, is one of the transcription factors of epithelial mesenchymal transition (EMT) [32]. In recent years, it has been found that SNAI2 is abnormally expressed in various kinds of malignant tumors and plays an important role in tumor progress and prognosis [33][34][35]. To investigate the role of SNAI2 in IM cells, we examined its expression level in IM tissues and BA-induced IM cells.…”
Section: Discussionmentioning
confidence: 99%
“…SNAI2 (also known as Slug), a member of Snail superfamily, is one of the transcription factors of epithelial mesenchymal transition (EMT) [32]. In recent years, it has been found that SNAI2 is abnormally expressed in various kinds of malignant tumors and plays an important role in tumor progress and prognosis [33][34][35]. To investigate the role of SNAI2 in IM cells, we examined its expression level in IM tissues and BA-induced IM cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among them are miR-30a [70], miR-122 [95], miR-182 [115], and miR-203 [115] and miR-204 [116]. SLUG is targeted in in oral squamous cell carcinoma by miR-204 [116]; glioblastoma by miR-203 [117]; in lung cancer by miR-1 [118]; in breast cancer by miR-124 [119,120], miR-30a [70], miR-497 [121], miR-1271 [122], and miR-203 [123,124]; in gastric cancer by miR-33a [125]; in lung cancer by miR-218 [126]; in clear cell renal cell carcinoma by miR-1 [127]; in osteosarcoma by miR-124 [128]; and in gingival fibroblasts by miR-200b [129]. Similarly to SNAIL, miRNAs-SLUG action regulates EMT in cancer progression, as well as different processes, such as the modulation of cancer stem cells' activity.…”
Section: Regulation Of Slug Expression By Micrornasmentioning
confidence: 99%
“…Cancer/Cell Type References miR-1 lung cancer [118] miR-30a breast cancer [70] miR-33a gastric cancer [125] miR-124 breast cancer [119,120] osteosarcoma [128] glioma [130] miR-200b gingival fibroblasts [129] miR-203 glioblastoma [117] breast cancer [123,124] miR-204 oral squamous cell carcinoma [116] miR-218 lung cancer [126] miR-497 breast cancer [121] miR-630 dermal microvascular endothelial cells [131] miR-1271 breast cancer [122]…”
Section: Micrornamentioning
confidence: 99%
“…These miRNAs underscore the putative differences between different types of breast cancer [59]. The ERα-miR-1271-SNAI2 axis is involved in the regulation of transforming growth factor (TGF)-β-induced breast cancer progression [60]. miR-301a-3p and miR-129 have been shown to inhibit estrogen signaling through direct interaction with ESR1 and ESR2 genes, respectively [61,62].…”
Section: Mirnas and Er Function In Cancersmentioning
confidence: 99%